Child Care and Early Education : Good practice to support young children and their families - Lindon, Jennie (London : Thomson Learning, 2003)
Written from a more practical angle than many existing childcare textbooks, Jennie Lindon's student text uses scenarios to describe practice in realistic fictional settings drawn from the author's extensive experience.
Includes bibliographical references and index.
Keywords: Child care -- Great Britain; Early childhood education -- Great Britain; Education